Prediction of stock price direction with machine learning models - Kant Kaw Khin (Nanyang Technological University, 2024)
Machine Learning (ML) algorithms drew a great deal of attention in the recent years as promising models in time-series predictions, allowing investors to leverage on these computational abilities to perform stock analysis more efficiently. Stock analysis can be done through Technical Analysis (TA), Fundamental Analysis (FA) and Sentiment Analysis (SA).